Global-genome Nucleotide Excision Repair Controlled by Ubiquitin/Sumo Modifiers - Rüthemann, Peter; Balbo Pogliano, Chiara; Naegeli, Hanspeter (Frontiers in Genetics, 2016)
Global-genome nucleotide excision repair (GG-NER) prevents genome instability by excising a wide range of structurally unrelated DNA base adducts and crosslinks induced by chemical carcinogens, ultraviolet (UV) radiation or intracellular metabolic by-products. As a versatile damage sensor, xeroderma pigmentosum group C (XPC) protein initiates this generic defense reaction by locating the damage and recruiting the subunits of a large lesion demarcation complex that, in turn, triggers the excision of aberrant DNA by endonucleases. In the very special case of a DNA repair response to UV radiation, the function of this XPC initiator is tightly controlled by the dual action of cullin-type CRL4DDB2 and sumo-targeted RNF111 ubiquitin ligases. This twofold protein ubiquitination system promotes GG-NER reactions by spatially and temporally regulating the interaction of XPC protein with damaged DNA across the nucleosome landscape of chromatin. In the absence of either CRL4DDB2 or RNF111, the DNA excision repair of UV lesions is inefficient, indicating that these two ubiquitin ligases play a critical role in mitigating the adverse biological effects of UV light in the exposed skin.